Aplikasi Teknik Polymerase Chain Reaction (PCR) Menggunakan Primer Degenerate dan Spesifik Gen AV1 Untuk Mendeteksi Begomovirus Pada Tomat (Lycopersicon esculentum Mill.) - Tri J. Santoso; Sri H. Hidayat; M. Herman; , Sudarsono (Jurnal Hortikultura Indonesia, 2013)
ABSTRACTBegomoviruses infection has been reported and found in several important vegetable crops included  tomato.  Nevertheless,  the  information  of  detection and  identification  of  Begomovirus infecting  tomato  plants  in  some  of tomato  production  areas  using  PCR  technique  has  not  been widely reported.  The  objective  of  this  research  was  to  detect  Begomovirus infecting  tomatoes  in some of tomato production areas of East Java, Central Java, Special Province of Jogjakarta and West  Java  using  PCR  technique with degenerate  and  specific  primers.  PCR  amplification  of Begomovirus genome was conducted by using a pair of degenerate primers, i.e. PAL1v1978-F and PAR1c715-R  and  specific  primer,  AV1-F/R.  For  confirmation  the  virus, it  was  conducted  a  virus transmission from the symptomed plant tomato sampel to healthy plants by using whiteflies vector. The  results  of  this research  showed  that  the  symptomed  plants  collected  from  several tomato production  areas  of  East  Java,  Central  Java,  Special  Province  of Jogjakarta  and  West  Java indicated that those plants have been infected by Begomovirus following PCR detection using a pair of degenerate primers. The Begomovirus infection was indicated by the PCR amplified product with the size of 1500 bp.  The results of PCR amplification  using specific primers AV1-F/R to detect the genus  of  Begomovirus  showed  that  all  samples  of  plant collections  generated  of  780  bp  DNA fragment. Confirmation of the virus through transmission by  whitefiles  vectors in greenhouse from the symptomed plants and the positive PCR samples showed that the virus transmission process was succesfully conducted with indication of the emergence of symptoms in healthy plants.Keywords: tomato  ( Lycopersicon  esculentum  Mill.) ,  Begomovirus, PCR technique, degenerate primerABSTRAKHasil  penelitian  sebelumnya  menunjukkan  bahwa  Infeksi  virus begomovirus di  beberapa tanaman sayuran termasuk tanaman tomat. Namun demikian, penelitian yang memberikan informasi mengenai  deteksi  dan  infeksi  dari virus  begomovirus  yang  menginfeksi  tanaman  tomat  dengan menggunakan teknik  PCR  masih  perlu  diteliti  lebih  lanjut.  Tujuan  dari  penelitian  adalah untuk mendeteksi begomovirus yang menginfeksi  tanaman  tomat di beberapa daerah produksi tomat dari Jawa Timur, Jawa Tengah,  Yogyakarta,  dan Jawa Barat menggunakan teknik PCR dengan primer degenerate  dan  spesifik. Amplifikasi  PCR  genom  begomovirus  dilakukan  dengan menggunakan sepasang  degenerate  primer  yaitu  PAL1v1978-F  dan   PAR1c715-R,  serta  primer  spesifik  adalah AV1-F/R.   Konfirmasi  virus dilakukan  dengan  teknik  penularan  virus  oleh  vektor  kutu  kebul ke tanaman sehat. Hasil penelitian menunjukkan bahwa  sampel-sampel tanaman tomat bergejala yang dikoleksi  dari  beberapa  daerah  di  Jawa Timur,  Jawa  Tengah,  Jawa  Barat  dan  D. I . Jogjakarta mengindikasikan adanya infeksi oleh Begomovirus setelah dideteksi menggunakan teknik PCR dengan primer degenerate.  Hasil amplifikasi PCR menggunakan primer spesifik AV1-F/R untuk mendeteksi  genus Begomovirus  menunjukkan  bahwa  semua sampel  tanaman  koleksi  menghasilkan  amplikon  yang berukuran  780  bp. Konfirmasi  virus  melalui  penularan  dengan  vektor  kutu  kebul  di  rumah kaca  dari sampel  tanaman  sakit  dan  positif  PCR  menunjukkan  terjadinya proses  penularan  virus  yang  ditandaidengan munculnya gejala-gejala pada tanaman yang sehat.Kata kunci: Begomovirus, Lycopersicon esculentum, Primer degenerate, Tehnik PCR.